Prognosis of training effects based on somatic characteristics and sport result - Klimczyk, M.; Klimczyk, A. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: Researchers and coaches continue to look for the solutions that would contribute to creation of somatic and mobility condition patterns, allowing the players to obtain sport achievements at the highest level. Therefore, the aim of the study was to trace the sport results` impact in the pole vault and the selected somatic parameters of the vaulters of different ages and comparing them with the results of the players reaching the results at the highest level.